Comparison between Japanese online and standard administrations of the Gudjonsson Suggestibility Scale 2 and effects of post-warning - Wachi, Taeko (Legal and criminological psychology, 2019)
Purpose. This study aimed to develop the Japanese online version of the Gudjonsson Suggestibility Scale 2 (GSS2). The effects of post-warning and free recall on suggestibility were also examined. Methods. A total of 442 people aged between 20 and 59 years took the Japanese online version of the GSS2, and their scores were compared with those obtained via administration of the Japanese standard version in a previous study and those of the British normative sample. The influence of post-warning (a technique in which the participant is given an apology for the incorrect negative feedback provided on the first day) and free recall instruction on suggestibility was examined in 10 out of the 20 GSS test questions 2 days after the administration of the online GSS2. Results. There were no differences in Yield2, Shift, and Total suggestibility scored between the Japanese online and standard versions of the GSS2. The difference in Yield1 scores between the two versions was also small. However, there were significant differences between the Japanese online and British versions in all GSS scores other than Total suggestibility. Further, post-warning and free recall effectively avoided an increased number of misled responses to leading questions. Conclusions. The results obtained demonstrate the validity of the Japanese online version of the GSS2. It was also found that certain instructions could be used to prevent further response suggestibility when any misleading questions were provided.